STUDI KAPASITAS ADSORPSI-REDUKSI ION Au(III) PADA ASAM HUMAT HASIL ISOLASI DARI TANAH GAMBUT RAWA PENING - Prasasti, Dian; Juari, Sri; Sudiono, Sri (Pharmaciana, 2012)
Isolation of peat soil humic acid and its application for adsorption-reduction ofAu(III) have been conducted. Humic acid was isolated from peat soil that was collectedfrom Rawa Pening, Central Java. Isolation of humic acid from peat soil was based onconventional alkaline extraction. Humic acid was extracted from peat soil with NaOH0.1 M, then precipitated with 0.1 M HCl, and purified with 0.1 M HCl/0.3 M HF 1/1.The isolated humic acid was characterized by FTIR spectroscopy, then applied foradsorption reduction of Au(III). Isothermic adsorption capacity on adsorptionreduction process of Au (III) also were studied. The gold metal formed was confirmedby XRD diffractogram, and photo optical microscope. The adsorption capacity withLangmuir isothermic model for humic acid was 192 mg/g. Peaks of gold particles in thedifractogram are 2 = 38, 44, and 64.